Knowledge of Safe Swaddling Practices among Mothers of Neonates Visiting a Tertiary-Care Hospital in a Developing Country - Saffi Ullah; Asif Rehman; Umair Qazi; Ayesha Abdullah; Azhar Zahir Shah; Abdul Jalil Khan; Mahvash Zeb (Gandhara University, 2023)
OBJECTIVES Swaddling of new-borne and infants remains common in the developing world, but little is known about maternal knowledge of swaddling. Therefore, this study aimed to determine the level of knowledge of safe swaddling practices among mothers of neonates visiting a Tertiary-Care Hospital. METHODOLOGY This cross-sectional study was conducted in the paediatric unit of tertiary care hospital in Peshawar city, Pakistan, between July and December 2018. A total number of 370 mothers of neonates who volunteered their participation were selected using a non-probability consecutive sampling technique. The study was based on a questionnaire comprised of socio-demographic and other questions related to the knowledge of safe swaddling practices. RESULTS A total number of 370 mothers of neonates knowledge were assessed. The study participants ranged between 17 - 49 years, with a mean age of 27.14 (SD ± 5.46). Of the total, 365 (98.6%) mothers were swaddling their babies, while only 5 (1.3%) reported not practising swaddling. Most mothers (51.1%) had good knowledge, while 44.3% had adequate knowledge, and only 4.6% had insufficient knowledge regarding safe swaddling. Knowledge of safe swaddling increased with age and parity. Most mothers (90%) correctly identified that "cotton cloth or light blanket should be used to swaddle baby". CONCLUSION It is concluded from this study that most mothers have adequate knowledge about safe swaddling, and the level of knowledge increases with age and parity. Safe swaddling techniques and information should be given to mothers at the beginning of antenatal care to benefit from its positive outcomes and, at the same time to avoid its drawbacks.